Bringing bioactive compounds into membranes: the UbiA superfamily of intramembrane aromatic prenyltransferases - Li, Weikai (Trends Biochem Sci, 2016)
The UbiA superfamily of intramembrane prenyltransferases catalyzes a key biosynthetic step in the production of ubiquinones, menaquinones, plastoquinones, hemes, chlorophylls, vitamin E, and structural lipids. These lipophilic compounds serve as electron and proton carriers for cellular respiration and photosynthesis, as antioxidants to reduce cell damage, and as structural components of microbial cell walls and membranes. This article reviews the biological functions and enzymatic activities of representative members of the superfamily, focusing on the remarkable recent research progress revealing that the UbiA superfamily is centrally implicated in several important physiological processes and human diseases. Because prenyltransferases in this superfamily have distinctive substrate preferences, two recent crystal structures are compared to illuminate the general mechanism for substrate recognition.